Does academic performance influence personal growth initiative? An institutional-based study among undergraduate dental students - Shiva Kumar Patanapu; Dolar Doshi; Suhas Kulkarni; Padma Reddy; Srilatha Adepu; Srikanth Reddy (Wolters Kluwer Medknow Publications, 2018)
Introduction: Personal growth initiative (PGI) is an "intentional involvement in changing and developing as a person." A student who has higher level of PGI is said to show higher academic performance because higher level of PGI might increase the student's contribution and achievement in life. Aim: This study aimed to explore the association between academic performance and PGI among undergraduate dental students. Methods: A cross-sectional study was carried out among 287 2nd, 3rd, 4th year dental students and interns of Panineeya Institute of Dental Sciences, Dilsukhnagar, Hyderabad. Personal growth was evaluated by Personal Growth Initiative Scale-II (PGIS-II) along with their university academic performance in the last year. SPSS package version 21.0, Kruskal-Wallis test, and Mann-Whitney U-test were used for comparison among variables. Results: A significant difference (P = 0.05) was observed for PGIS subscale "readiness for change," with a higher mean score among 4th-year students (3.59 ± 1.07). However, females showed higher mean score for all subscales of PGIS except "Using resources" and total PGIS, but there is no significant gender difference. While higher mean scores for all subscales and total PGIS were observed among students who attained > 75% in their last year university examination, significant difference was observed for subscale "Intentional behavior" (P = 0.02) only. Conclusion: PGI scale plays a crucial role among students to experience increased levels of well-being, develop them positively, and adapt to adverse situations.